Differences between frequent emergency department users in a secondary rural hospital and a tertiary suburban hospital in central Japan: a prevalence study - Makoto Kaneko; Masashi Okubo; Michael D Fetters; Machiko Inoue; Allison K Cullen Furgal; Benjamin F Crabtree (BMJ Open, 2020)
Objectives Although frequent emergency department (ED) use is a global issue, little research has been conducted in a country like Japan where universal health insurance is available. The study aims to (1) document the proportion of ED visits that are by frequent users and (2) describe the differences in characteristics of frequent ED users and other ED users including expenditures between a secondary and a tertiary hospital.Design A prevalence study for a period of 1 year.Setting A secondary hospital and a tertiary hospital in central Japan.Participants All patients who presented to the EDs.Primary outcome measures We defined frequent ED user as a patient who visited the ED≥5 times/year. The main outcome measures were the proportion of frequent ED users among all ED users and the proportion of healthcare expenditures by the frequent ED users among all ED expenditures.Results Of 25 231 ED visits over 1 year, 134 frequent ED users accounted for 1043 visits—0.66% of all ED users, comprised 4.1% of all ED visits, and accounted for 1.9% of total healthcare expenditures. Median ED visits per one frequent ED user was 7.9. At the patient level, after adjusting for age, gender and receiving public assistance, older age (OR 1.01, 95% CI: 1.00 to 1.02) and receiving public assistance (OR 7.19, 95% CI 2.87 to 18.07) had an association with frequent ED visits. At the visit-level analysis, evaluation by internal medicine (OR 1.27, 95% CI 1.02 to 1.57), psychiatry (OR 124.69, 95% CI 85.89 to 181.01) and obstetrics/gynaecology (OR 2.77, 95% CI 2.09 to 3.67) were associated with frequent ED visits.Conclusion The proportion of frequent ED users, of total visits, and of expenditures attributable to them—while still in the low end of the distribution of published ranges—are lower in this study from Japan than in reports from many other countries.